Capability vs Popularity: A Case Study of Placing Celebrities as Commission Members in The DPR RI - Sandrina Reswara (Yayasan Taslim Madayana Indonesia, 2026)
Background. There is a growing trend in Indonesian politics where celebrities are elected to the House of Representatives (DPR RI) due to their popularity rather than political or legislative competence. This reflects a shift in electoral dynamics, where public recognition is prioritized over qualifications, raising concerns about the effectiveness of legislative performance. .Purpose. The study aims to analyze the gap between popularity and capability among celebrity legislators in Indonesia, with a focus on their placement in parliamentary commissions. It seeks to explore how descriptive representation (based on identity or appearance) may conflict with substantive representation (based on actual performance and advocacy). Method. This research uses a qualitative case study method, focusing on Ahmad Dhani as a key example. It also applies comparative analysis by referencing best practices from the United States, and evaluates political party recruitment strategies through academic and media sources. Results. The findings indicate that celebrity status does not ensure legislative competence. The study concludes that political recruitment must be reformed toward a merit-based system, and recommends legislative and ethical training for elected representatives to enhance the quality of democracy and governance in Indonesia. Conclusion. Celebrity status alone does not guarantee legislative competence. To strengthen representative democracy in Indonesia, political recruitment must prioritize merit over popularity and include proper legislative and ethical training for elected officials.